Hlapivi spojevi arome kupreške janjetine - Krvavica, Marina (Array, 2020)
Within the project of determining the aroma profiles of various Croatian lamb species, whose main objective was to offer a simple and reliable analytical method that could confirm their authenticity by linking them to a geographical breeding area, an analysis of volatile compounds of the Kupres lamb grown on the Kupres Plateau (BiH), at about 1200 m above sea level, was carried out. The considerable territorial separation (horizontal and vertical) of the Kupres Plateau from the Croatian territories where the study was organised (Lika, Dalmatian hinterland, the islands of Pag and Cres) and the differences in their natural characteristics contribute to the reliability of drawing conclusions about possible lamb biomarkers that could be associated with the floral composition of a geographical breeding area. A total of 66 volatile compounds were isolated by the GC-MS analysis (SPME method) of heat-treated Kupres lamb, of which 14 aldehydes (61.55 % of the total peak area), 10 alcohols (7.78 %), 12 ketones (12.11 %), 8 aliphatic hydrocarbons (1.23 %), 7 aromatic compounds (9.63 %), 3 heterocyclic compounds (0.95 %), 1 furan (1.34 %), 2 acids and 3 esters (3,75 %), 4 terpenes (0.94 %) and 3 sulphur compounds (0.73 %). In relation to Dalmatian, Pag, Lika and Cres lamb, the aroma of Kupres lamb contains 3 volatile compounds (2 ketones and 1 ester) which have not been identified in the mentioned types of lamb. Furthermore, the aroma of Kupres lamb contains notably more C-7 aldehydes (16.24 %), ketones 2,3-octadienone and 2-octanone (9.96 %) and long-chain alkanes (0.71 %), that are reported by other researches as pasture markers, but also a much smaller amount and content of terpenes (0.94 %), that are reported as possible reliable biomarkers of the geographical breeding area. Since terpenes are solely metabolites of plants (dicotyledons contain much more terpenes than monocotyledons), mainly incorporated directly from food into animal tissues, the terpenic profile of